2022
DOI: 10.1002/asia.202200563
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime‐Based Responsive Probes: Design and Applications in Biological Analysis

Abstract: With the development of modern biomedicine, biological analysis and detection are very important in disease diagnosis, detection of curative effect, prognosis and prediction of tumor recurrence. Compared with the currently widely used optical probes based on intensity signals, the lifetime signal does not depend on the influence of conditions such as the concentration of luminophore, tissue penetration depth and measurement method. Therefore, biological detection methods based on lifetime-based re-sponsive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…In fluorescence lifetime ISM (FLISM), 6 , 9 the photon arrival time with respect to the fluorophore excitation event enables mapping the fluorescence lifetime distribution in the sample at superresolution. Such information helps us understand the properties of the biomolecular environment, 18 decipher biomolecule structural changes, 19 and implement multispecies imaging 20 . In quantum ISM (Q-ISM), 5 the photon coincidences allow the construction of an image with a spatial resolution beyond the limits of conventional ISM.…”
Section: Introductionmentioning
confidence: 99%
“…In fluorescence lifetime ISM (FLISM), 6 , 9 the photon arrival time with respect to the fluorophore excitation event enables mapping the fluorescence lifetime distribution in the sample at superresolution. Such information helps us understand the properties of the biomolecular environment, 18 decipher biomolecule structural changes, 19 and implement multispecies imaging 20 . In quantum ISM (Q-ISM), 5 the photon coincidences allow the construction of an image with a spatial resolution beyond the limits of conventional ISM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of fluorescent probes for quantitative measurements in conventional fluorescence confocal microscopy presents several limitations such as dependence on fluorophore concentration, excitation source intensity and duration of light exposure, among others [19][20][21]. In contrast, interest in fluorescence lifetime imaging microscopy (FLIM) has increased in the last years because it is both an imaging technique and an absolute measurement method that allows obtaining reproducible concentrations of diverse biological analytes [20,22,23]. Thus, some examples of fluorescence lifetime probes for intracellular pH measurements have been reported in the last decade [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…As fluorescence lifetime is an intrinsic property of fluorescence probes, FLIM is not influenced by concentration variations, which can be affected by cell volume changes or photobleaching . Additionally, the sensitivity of fluorescence lifetime to microenvironments enables the visualization and quantification of biophysical parameters such as polarity and viscosity within cells. Thus, two-photon FLIM (TP-FLIM) is a valuable tool for measuring changes or differences of microenvironments in subcellular regions or in vivo . To our knowledge, although a few studies have reported the correlation between the polarity change of LDs and the fluorescence lifetime by using one-photon FLIM, , no research has yet reported the polarity differences of LDs in vitro and in vivo by using TP-FLIM. In this study, TBPCPP, a polarity-sensitive two-photon fluorescence lifetime probe for LDs with a donor (D)-acceptor (A)-π-acceptor (A) structure was designed and synthesized by using a facile method (Scheme ).…”
Section: Introductionmentioning
confidence: 99%